M Model Pembelajaran APPOSITE Berbantuan Video Animasi dalam Meningkatkan Hasil Belajar dan Kemampuan Berpikir Tingkat Tinggi Siswa pada Materi Fluida Statis - Wuragil, Aprillia Kartika Agit; Prastowo, Sri Handono Budi; Maryani, Maryani (Universitas Nurul Huda, 2021)
Application of learning model APPOSITE (Application of Step Instruction and Elaboration) with animation videos on this research have to purpose a differents enhancement study result and higher order thinking skill (HOTS) student on fluida statis. Research types is pre-experiment with one group pretes-posttes design. research subject is XI MIPA 6 Student of senior high school 1 Pesanggaran Banyuwangi, with one class experiment which choosed by Fisika’s teacher. Acquisition technique data is interview, documentation, pretes, student worksheet, and posttes. Analysis technique data research is use descriptive analysis to know higher order thinking skill, t-test to know enhancement study result of APPOSITE model with videos animation. Subsequently supported with account n-gain from pretes-posttes score experiment class. Based on result this research, APPOSITE learning model with animation video have a good effect and enhancement higher order thinking skill (HOTS) student, and model is effective enough to enhancement study result student. This is also supported of the result n-gain is obtained 0,639.